Unexpected patterns of genetic connectivity in Lobophyllia corymbosa (Forskål, 1775) around Sulawesi, Indonesia - Widyastuti Umar; ASMI CITRA MALINA A.R. TASSAKKA; Paul Henry Barber; Jamaluddin Jompa (Society for Indonesian Biodiversity, 2019)
Abstract. Umar W, Tassakka ACMAR, Barber PH, Jompa J. 2019. Unexpected patterns of genetic connectivity in Lobophyllia corymbosa (Forskål, 1775) around Sulawesi, Indonesia. Biodiversitas 20: 2744-2749. Sulawesi is a strategic area for the biological networks of marine organisms, especially for Scleractinian corals. Sulawesi is located centrally in Indonesia and influenced by Pacific and Indian Ocean currents and shown in unique biodiversity patterns. However, research in this region is very limited. The wide distribution and lack of information on dispersal and connectivity make Lobophyllia corymbosa an exciting candidate in this study for genetic connectivity at the heart of the Indonesian Coral Triangle Area (ICTA), using Mitochondrial DNA (mtDNA) genome. Sampling sites (Palu, Mamuju, Sinjai, and Luwuk Banggai) with different coral fragments were collected from each site, DNA extracted, and mitochondrial COI gene was amplified. The results of the analysis were unexpected, and we hypothesise that the observed pattern was due to the evolution of different lineages within this region. The distance index and genetic diversity showed a close relationship between Mamuju and Luwuk Banggai, while Sinjai and Palu had a different genetic pattern. The global current patterns, complicated geography, and habitat condition could lead to such an outcome. Hard coral larvae arriving in an area might bypass a number of possible